Ulli Beier-Schrein in Sydney (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Art; Artists; Interior decoration; Sculpture; Photographs; Masks; Shrine; Yoruba Art; Sydney; Art Collector; Art Collecting; Wood Sculpture